An Analysis of Pregnancy-Related Anxiety Using a Biopsychosocial Approach - Darmayanti Wulandatika; Siti Fatimah; Dyta Setiawati Hariyono; Ramadhana Alya Nuur Afifah; Nadila Azkiya (The Indonesian Institute of Science and Technology Research, 2025)
Psychological disorder in women is one of the most common health problems in women worldwide. When not addressed properly, anxiety can affect maternal and neonatal health. In the biopsychosocial model, mental health is influenced by biological, psychological, and social factors, so a comprehensive approach to mental health services for women during pregnancy is needed. This study aims to analyze anxiety in pregnant women using the biopsychosocial model approach. This study used a mixed-methods research design using a qualitative cross-sectional approach using the Perinatal Anxiety Screening Scale (PASS) instrument and a generic exploratory approach. In this qualitative research stage, in-depth interviews were conducted to explore biological, psychological, and social factors. The collected data was subjected to analysis using the Braun & Clarke approach. Responses were obtained from 385 pregnant women. 62.1% women had anxiety in pregnancy and reporting feeling anxiety caused by body changes, psychological changes and social adaptation during their pregnancy. In multivariate logistic regression, the incidence of anxiety during pregnancy was strongly associated with age (OR = 2.53; 95% CI = 1.57 – 4.09), parity (OR = 2.51; 95% CI = 1.61 – 3.92), and employment status (OR = 1.74; 95% CI = 1.09 – 2.77). The existence of physical, emotional, and social changes during pregnancy has an impact on the emergence of anxiety during pregnancy. The importance of support during pregnancy from health professionals, the environment and cross-sectoral collaboration is expected to reduce the incidence of anxiety during pregnancy.